A 200-year history of arctic and alpine fungi in North America: Early sailing expeditions to the molecular era. Issue 1 (1st January 2020) - Noffsinger, Chance; Cripps, Cathy L.; Horak, Egon
ABSTRACT: Mushrooms and other fleshy fungi are important components of arctic and alpine habitats where they enhance nutrient uptake in plants and replenish poor soils through decomposition. Here we assemble the 200-year (1819–2019) record of their discovery in North America, beginning with early Arctic sailing expeditions, followed by intense taxonomic studies, and concluding with the molecular era, all of which highlight the difficulty of exhaustively revealing their biodiversity in these extreme, cold-dominated habitats. Compiled biogeographic data reveal that a majority of arctic fungi have large intercontinental distributions with disjunct alpine populations. A newly compiled checklist of 170 species of Basidiomycota in fifty-one genera and twenty families in the Rocky Mountain alpine zone provides current baseline data prior to expected environmental shifts.